Unravelling the Potamonautes lirrangensis (Rathbun, 1904) species complex (Potamoidea: Potamonautidae), with the description of two new species - Cumberlidge, Neil; Johnson, Emily; Clark, Paul F.; Genner, Martin J. (European Journal of Taxonomy, 2021)
The taxonomic status of the widely distributed freshwater crab Potamonautes lirrangensis (Rathbun, 1904) sensu lato is revised because morphological and molecular evidence indicates that this taxon is a complex comprising more than one species. Four taxa are now recognized: Potamonautes lirrangensis (Rathbun, 1904) s. str. and P. kisangani sp. nov. from the Middle Congo River in Central Africa, P. amosae sp. nov. from the drainages of Lakes Kivu and Tanganyika, and P. orbitospinus (Cunnington, 1907) from Lake Malawi which had been previously synonymised with P. lirrangensis s. lat. Diagnoses, illustrations and distribution maps are provided for each of these taxa and they are compared to similar species from Central and Southern Africa.